Matching espacial para georreferenciar datos de encuestas de hogar - Mónica Navarrete; Patricio Aroca; Jorge Bernal (Estudios de Economía, 2017)
– This paper develops a methodology using business intelligence (data warehouse) and OLAP tools (Online Analytical Processing) to match individuals from a household survey data to a census one. In order to geo-reference the household data, the method takes advantage of the geographical information of the census. Using the 2003 Household Survey and the 2002 Chilean Census of Population and Housing, the average household income is projected to intra-municipality levels and the results are compared to Elbers et al. (2003) methodology. The results show that the proposed methodology allows for taking into account and display the impact of intra-municipality heterogeneity and the spatial interaction among the spatial units.
Keywords: C5; C63; C81; 330; Spatial Matching; Small Areas Estimation; Household Surveys; Household Income; Business Intelligence